BABEL (Better tArgeting, Better outcomes for frail ELderly patients) advance care planning: a comprehensive approach to advance care planning in nursing homes: a cluster randomised trial. (23rd March 2022) - Garland, Allan; Keller, Heather; Quail, Patrick; Boscart, Veronique; Heyer, Michelle; Ramsey, Clare; Vucea, Vanessa; Choi, Nora; Bains, Ikdip; King, Seema; Oshchepkova, Tatiana; Kalashnikova, Tatiana; et al.
Abstract: Background: Nursing home (NH) residents should have the opportunity to consider, discuss and document their healthcare wishes. However, such advance care planning (ACP) is frequently suboptimal. Objective: Assess a comprehensive, person-centred ACP approach. Design: Unblinded, cluster randomised trial. Setting: Fourteen control and 15 intervention NHs in three Canadian provinces, 2018–2020. Subjects: 713 residents (442 control, 271 intervention) aged ≥65 years, with elevated mortality risk. Methods: The intervention was a structured, $\sim$ 60-min discussion between a resident, substitute decision-maker (SDM) and nursing home staff to: (i) confirm SDMs' identities and role; (ii) prepare SDMs for medical emergencies; (iii) explain residents' clinical condition and prognosis; (iv) ascertain residents' preferred philosophy to guide decision-making and (v) identify residents' preferred options for specific medical emergencies. Control NHs continued their usual ACP processes. Co-primary outcomes were: (a) comprehensiveness of advance care planning, assessed using the Audit of Advance Care Planning, and (b) Comfort Assessment in Dying. Ten secondary outcomes were assessed. P-values were adjusted for all 12 outcomes using the false discovery rate method. Results: The intervention resulted in 5.21-fold higher odds of respondents rating ACP comprehensiveness as being better (95% confidence interval [CI] 3.53, 7.61). Comfort in dying did not differ (difference = −0.61; 95% CI −2.2, 1.0). Among the secondary outcomes, antimicrobial use was significantly lower in intervention homes (rate ratio = 0.79, 95% CI 0.66, 0.94). Conclusions: Superior comprehensiveness of the BABEL approach to ACP underscores the importance of allowing adequate time to address all important aspects of ACP and may reduce unwanted interventions towards the end of life.